Penanaman Nilai Nasionalisme melalui Literasi Fikih Kebangsaan di Ma’had Aly Lirboyo Kota Kediri - Naim, Ainun; Taulabi, Imam; Ubaidilla, Syafik (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2024)
This research aims to understand the process of instilling nationalist values ​​through nationalism fiqh literacy at the Ma'had Aly Lirboyo, Kediri City. This study employs qualitative research methods. The main data source is interviews with mudir, mustahiq, munawwib, administrators, the graduates, and mahasantri Ma'had Aly Lirboyo. This research had three findings. First, the genealogy of nationalist values ​​in nationalism fiqh literacy in Ma'had Aly Lirboyo is rooted in the nationalism spirit of the kiais (masyayikh) of Pesantren Lirboyo. Second, the internalization methodology was formulated by studying bahtsul masail and Al-Mahalli deliberation and interpreting national verses and hadith using the ushul fiqh and fiqh rules approach. Third, the impact of internalization can be seen from two types of contributions: intellectual contributions in the form of scientific works by mahasantri for each generation (graduate), which are published every year, and practical contributions in the form of mahasantri's work in a society with a tolerant attitude, particularly while coexisting with adherents of different faiths or religions.